Investigating the Elements Influencing the Identification of “At-Risk” Students in the Context of the Full-Day Early Learning - Kindergarten Program in Ontario - Gooderham, Suzanne (Université d'Ottawa / University of Ottawa, 2015)
This study was designed to explore the elements that influence the identification of young children that might be considered at-risk for early school failure. To this end, guided by complexity theory, the study sought to examine (a) system requirements and expectations at the provincial and school board levels, (b) current practice in schools and classrooms, and (c) the beliefs and knowledge of individuals surrounding the assessment and identification of at-risk students in Kindergarten. Using a qualitative, case-study approach 23 individuals from two different school boards in Ontario were interviewed to explore both practice and beliefs. Review of relevant provincial and school board documents as well as artifacts that were gathered during school visits provided further information. While there were some differences in details, the findings were similar in the two boards. In describing which characteristics were of concern when considering an at-risk designation, most participants cited social, emotional, and behavioural difficulties. While both school boards required tracking and assessment of literacy skills, teachers and ECEs concentrated more on ongoing observations and anecdotal notes to determine student progress. Interventions for students at-risk were more often provided for students with academic difficulties. However, there was also some support for behaviour difficulties in terms of consultation from special education personnel in one board and an early intervention team in the other. It was clear from the findings that many elements influence the identification of a student as at-risk including the characteristics of the student, the student’s family, and the particular classroom, school, and board the student attends. The study findings contribute to our understanding of practice and beliefs around young student at-risk and how the interactions of the various elements involved impact the identification of individual students.
Keywords: Early identification; At-risk; Kindergarten